2008
DOI: 10.1111/j.1600-6143.2007.02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Recurrent Henoch–Schönlein Purpura in a Renal Allograft with Plasmapheresis

Abstract: Acute and severe cases of Henoch-Schönlein purpura (HSP) nephritis have been treated with plasmapheresis (PA) in both adults and children. It has been used either alone or with steroids, antiplatelets or cytoxic drugs. Generally, renal function has been shown to improve when PA is utilized. The role of PA in recurrent HSP after renal transplantation is unclear and has not been well described in the literature. We report a 29-year-old female with HSP who developed end-stage renal disease and subsequently underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In our study, no specific treatment was administered in cases with recurrent HSN. Recently, a case report showed that plasmapheresis resolved recurrent HSN after kidney transplantation (21). However, there is no randomized study on the effect of treatment on recurrent HSN.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, no specific treatment was administered in cases with recurrent HSN. Recently, a case report showed that plasmapheresis resolved recurrent HSN after kidney transplantation (21). However, there is no randomized study on the effect of treatment on recurrent HSN.…”
Section: Discussionmentioning
confidence: 98%
“…Plasmapheresis might be effective by removing antibody complexes before as well as after their deposition in mesangium [10]. Unfortunately we did not have antibody titers in our patient to make a comparison.…”
Section: Discussionmentioning
confidence: 94%
“…Several case series suggest that high‐dose corticosteroid therapy, often in combination with immunosuppressive agents such as cyclophosphamide and cyclosporine A, is effective at treating severe HSPN in the native kidney. A more recent report suggests that the addition of plasmapheresis may be of benefit to severe HSPN patients, even with recurrence after transplantation . However, these treatments had no effect on her native kidney.…”
Section: Discussionmentioning
confidence: 99%